ANALISIS KANDUNGAN KARBOHIDRAT TERLARUT TOTAL PLANLET JERUK KEPROK BW (Citrus reticulata Blanco) SETELAH DIINDUKSI LARUTAN ATONIK DALAM KONDISI CEKAMAN KEKERINGAN SECARA IN VITRO - Ni Made Nada Elsika; Endang Nurcahyani; Yulianty Yulianty; Sri Wahyuningsih (Agros Journal of Agriculture Science, 2023)
Tangerine BW (Citrus reticulata Blanco) is cultivated in lampung province. The obstacle is the low level of rainfall which causes water availability to decrease and soil conditions to become dry. Atonic is used as growth regulator. Peg 6000 can reduce osmotic potential so that water availability is reduced and mimic drought stress conditions. This study aims to determine the carbohydrate content of bw orange planlets that are resistant to drought stress. this research was conducted from January to march 2021 in the in vitro room botany laboratory, department of biology, faculty of mathematics and natural sciences, university of lampung. This study used a factorial complete randomized design, consisting of 2 factors, namely atonic solution with 3 levels of treatment 0ml/l(a1), 3ml/l(a2) and 6ml/l(a3) and PEG 6000 with concentration levels of 0% and 10% with 4 replications. Homogeneity of variance using levene test at 5% real level, then continued with two way factorial anova at 5% real level and honest real difference further test at 5% level. The results showed that combination of 0ml/l atony and 10% peg 6000 can increase the total soluble carbohydrate content in bw orange planlets (Citrus reticulata Blanco).Keywords: atonyc; Citrus reticulata; peg 6000INTISARIJeruk BW (Citrus reticulata Blanco) dibudidayakan di Propinsi Lampung. Kendalanya adalah tingkat curah hujan yang rendah menyebabkan pasokan air menurun dan kondisi tanah menjadi kering. Atonik dipakai sebagai Zat Pengatur Tumbuh. PEG 6000 dapat menurunkan potensial osmotik sehingga ketersedian air berkurang dan menirukan kondisi cekaman kekeringan. Penelitian ini bertujuan untuk mengetahui kandungan karbohidrat planlet jeruk BW yang tahan cekaman kekeringan. Penelitian ini dilaksanakan Januari-Maret 2021 di ruang in vitro, Laboratorium Botani, Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Lampung. Penelitian ini menggunakan Rancangan Acak Lengkap Faktorial, yang terdiri dari 2 faktor yaitu larutan Atonik dengan 3 taraf perlakuan (0 mL/L (a1), 3 mL/L (a2), 6 mL/L (a3) ) dan PEG 6000 dengan taraf konsentrasi (0% dan 10%) dengan 4 kali ulangan. Homogenitas ragam menggunakan uji Levene pada taraf nyata 5%, kemudian dilanjutkan dengan Uji Two Way Factorial Anova pada taraf nyata 5% dan uji lanjut Beda Nyata Jujur pada taraf nyata 5%. Hasil penelitian menunjukkan Kombinasi PEG 6000 10% dan atonik 0% dapat meningkatkan kandungan karbohidrat terlarut total pada planlet jeruk BW (Citrus reticulata Blanco). Kata kunci : Atonik; Citrus reticulata; PEG 6000